The Dark Side of Dependency: Negative Consequences of EFL Students' Use of ChatGPT for Academic Writing - Marisa, Sonia; Rachman, Dzul; Puspita, Rani Herning; Rahmawati, Yeni (Borneo Educational Journal (Borju), 2025)
The need for artificial intelligence-based tools like ChatGPT is rising among EFL students in scientific writing, as these technologies enhance the efficiency and clarity of their written work. This study underscores the detrimental effects of over dependence on these tools, particularly regarding students' critical thinking skills, creativity, and academic integrity. Data was acquired by successively implementing a mixed-methods strategy, which involved delivering questionnaires to 60 students from the English Education program, followed by semi-structured interviews with chosen responders. Quantitative results indicate that although ChatGPT assists in generating ideas and enhancing grammar, its utilization frequently diminishes analytical depth, undermines the writer's authentic voice, and heightens the likelihood of plagiarism. Qualitative findings validated these results, as students articulated apprehensions regarding diminished creativity, drive to learn, and independent thought. This study finds that although ChatGPT might serve as a valuable resource, excessive dependence on it may impede the cultivation of students' intellectual faculties and ethical standards. Consequently, educational institutions must to establish explicit norms and promote the utilization of technology in a critical and ethical fashion. This study addresses a research deficiency by highlighting the adverse effects of AI utilization on EFL students' academic writing, a topic that has not been extensively explored previously.